1985
DOI: 10.1002/ar.1092110407
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes‐associated alterations in uterine structure in the C57BL/KsJ Mouse: Relationship to changes in estradiol accumulation, circulating ovarian steroid levels, and age

Abstract: The effects of the diabetes (D) mutation on utero-ovarian structure and function were examined in match-paired D and control (C) C57BL/KsJ mice between 2 and 16 weeks of age. Between 4 and 8 weeks of age, the uterine epithelium of D mice exhibited a remarkable increase in the amount of cytoplasmic lipid stores as compared with that of C animals. Associated with progressive hyperglycemia between 8 and 16 weeks of age, uterine atrophy and continued lipid accumulation occurred. Both serum progesterone and estradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 34 publications
0
63
0
Order By: Relevance
“…In addition, the failure of enhanced tissue noradrenergic counterregulatory responses (12,13) to modulate the observed structural and metabolic indexes, coupled with stimulated lipoprotein lipase enzyme activity indexes, indicates that the progressive lipid insult on cellular integrity promotes or induces cellular lipoatrophy, which then generates endometrial cellular regression and subsequent reproductive tract involution. These results suggest that the reproductive decline characteristic of many type 2 diabetes models, including humans, may be related to the noted cellular lipoadiposity and metabolic alterations that occur after chronic exposure to the hyperglycemic-hyperinsulinemic environment and the inability of recognized counterregulatory systemic factors to correct these homeostatic insults to cellular function (1,3,12,13). Previous studies have indicated that some of the structural features characterized in the present studies may be stabilized in the db/db model by endocrine replacement therapy of the affected female reproductive tract parameters, if therapy is initiated before the early onset of the syndrome expression (5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the failure of enhanced tissue noradrenergic counterregulatory responses (12,13) to modulate the observed structural and metabolic indexes, coupled with stimulated lipoprotein lipase enzyme activity indexes, indicates that the progressive lipid insult on cellular integrity promotes or induces cellular lipoatrophy, which then generates endometrial cellular regression and subsequent reproductive tract involution. These results suggest that the reproductive decline characteristic of many type 2 diabetes models, including humans, may be related to the noted cellular lipoadiposity and metabolic alterations that occur after chronic exposure to the hyperglycemic-hyperinsulinemic environment and the inability of recognized counterregulatory systemic factors to correct these homeostatic insults to cellular function (1,3,12,13). Previous studies have indicated that some of the structural features characterized in the present studies may be stabilized in the db/db model by endocrine replacement therapy of the affected female reproductive tract parameters, if therapy is initiated before the early onset of the syndrome expression (5).…”
Section: Discussionmentioning
confidence: 99%
“…Uteri from control and db/db matchedpaired groups ages 4, 8, 12, and 16 weeks were collected, weighed, and prepared for light and transmission electron microscopic (TEM) examination, as previously described (1)(2)(3)(4)(5). Tissue samples were sectioned and stained with toluidine blue for polychromatic lipid identification (1,3,20) and localization by light microscopic examination or with osmium tetroxide (4,5) before TEM examination. Tissue sections prepared for light microscopic analysis were used for cytoplasmic polychromatic organelle designation, localization of intracellular lipid inclusion accumulations, and subsequent determination of the cytoplasmic volume changes that occur with progressive diabetes, as previously described (5).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations